Digital Culture and Individuals: (Analysis of the influence of digital culture on individuals) - Ruli Aprilia (Jurusan Ilmu Komunikasi UTM, 2023)
The public sphere in the internet age is shaped by changes in traditional information consumption practices. With the rise of social media and other online platforms, the ways in which people access and consume information have shifted significantly. One major change is the increased role of user participation in shaping the public sphere. The online users are forced to act and participate. Currently media users are active and looking for information. The World Wide Web is a giant external memory, capable of storing a lot of information. Data can be by all. Even if the use of books for five centuries made linear thinking the primary means of reasoning, now it is gradually replaced by multitask, nonlinear, more thinking faster, more fluid and shallower at the same time. Internet users who relying on this external memory has better data analysis capacity, but does not have more synthesis capacity. External memory in the world wide web becomes